Disruption by design? Classification framework for the archetypes of disruptive business models - Alexander Lennart Schmidt; Peter van der Sijde (R&D Management, 2022)
The current scholarly debates highlight the role of business models for understanding the dynamics inherent to disruptive innovations. Additionally, research on business models argues for similarities between business models, as they are shared by multiple competitors and across industries. Despite the recent advancements in both debate streams, a consolidation of the research on the underlying similarities of disruptive business models is lacking. Such a consolidation would allow learning from previous waves of disruption, ultimately informing theory and practice to cope with the increasing pace and impact of disruptive innovations. Consequently, this study systematically identifies 122 disruptive business models that have been discussed in the literature during 2006–2019. Based on qualitative content analysis, we then develop a classification framework and propose five archetypes of disruptive business models: (1) matchmakers, (2) standardizers, (3) service providers, (4) open collaborators, and (5) performance reducers. We make a twofold contribution to the discussions around the hitherto tentatively specified business models underlying disruptive innovations, thus emphasizing the contingency of the phenomenon. First, we discuss how the identified archetypes are inducing disruptive dynamics. Second, we elaborate on how the archetypes are constituting paths towards disruption.
Keywords: 650